2017
DOI: 10.3892/etm.2017.4194
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the maintenance of stemness, viability, and differentiation potential of gingiva-derived stem-cell spheroids

Abstract: Gingiva-derived stem cells have been applied for tissue-engineering purposes and may be considered a favorable source of mesenchymal stem cells as harvesting stem cells from the mandible or maxilla may be performed with ease under local anesthesia. The present study was performed to fabricate stem-cell spheroids using concave microwells and to evaluate the maintenance of stemness, viability, and differentiation potential. Gingiva-derived stem cells were isolated, and the stem cells of 4×105 (group A) or 8×105 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Various materials can be used for the surface of microwells, including polyethylene glycol, polydimethylsiloxane, and polyurethane ( 20 , 21 ). The morphology can be modified by the shape of the microwells ( 10 ), and the size of the spheroids can also be controlled by the number of applied cells ( 5 ). Three-dimensional cultures can be made with the aid of scaffolds including alginate ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various materials can be used for the surface of microwells, including polyethylene glycol, polydimethylsiloxane, and polyurethane ( 20 , 21 ). The morphology can be modified by the shape of the microwells ( 10 ), and the size of the spheroids can also be controlled by the number of applied cells ( 5 ). Three-dimensional cultures can be made with the aid of scaffolds including alginate ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional spherical spatial boundary conditions have been reported to regulate the differentiation of mesenchymal stem cells ( 8 ). Moreover, three-dimensional culture system can be used for the evaluation of intercellular interactions in the regulation of cell proliferation and differentiation ( 9 , 10 ). Doxorubicin is reported to suppress bone marrow stem cells while expanding cancer stem cells ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In more recent years, three-dimensional cell culture methods have been widely applied and are regarded to have high importance in evaluating the biological processes [12]. Three-dimensional culture systems may simulate the intercellular interactions in regulation of stem cell self-renewal and differentiation [13]. It was shown that a three-dimensional culture enhanced the production of extracellular matrix-related genes when compared with two-dimensional monolayer culture [12].…”
Section: Three-dimensional Culturementioning
confidence: 99%
“…10 These stem-cell spheroids maintained the viability and stemcell characteristics of stem-cell surface-marker expression and differentiation potential. 11 In a previous study, cell spheroids from gingival cells and osteoprecursor cells were shown to be a promising strategy for stem-cell therapy. 12 The current study was therefore performed to evaluate the effects of simvastatin on cellular viability, stemness and osteogenic differentiation using 3-dimensional cell spheroids of stem cells and osteoblast-like cells.…”
mentioning
confidence: 99%